Validation of the Intuitive Eating Scale in pregnancy. (April 2018) - Paterson, Helen; Hay-Smith, Jean; Treharne, Gareth; Herbison, Peter; Howarth, Caroline
The objective of this study was to examine the content validity and test–retest reliability of the Intuitive Eating Scale among pregnant women. A qualitative think-aloud study of the Intuitive Eating Scale analysed the content validity. Overall, the Intuitive Eating Scale made sense to pregnant women, but food safety affected the interpretation of some items. A version with instructions modified accounting for food safety, the Intuitive Eating Scale–Pregnancy, was subsequently shown to have stable scores over 5 weeks during the second trimester, mean change = −0.08 (95% limits of agreement: −0.61 to 0.45), r  = 0.79, n  = 240. The Intuitive Eating Scale–Pregnancy was acceptable for use in this New Zealand pregnant population.